(untitled) (Proceedings of the International Conference on Future of Women, 2025)
Widows in rural Indonesia, tethered by the invisible threads of tradition, navigate a landscape where patriarchal norms cast long shadows over their autonomy and rights. This article explores the experience of three widows living in three villages in rural West Java, Central Java, and Central Kalimantan. It examines how their lives have changed since the adoption of the Beijing Declaration 30 years ago. Using a narrative approach, the research zooms into the personal stories of these women to understand their experiences with social attitudes, their role within the community, and their strategies for dealing with economic deprivation. Observation and in-depth interviews were conducted to collect the data. The validity of the instrument was confirmed with a Cronbach’s alpha coefficient of 0.89 while the validity of the DBR process was strengthened through qualitative data triangulation. The results of the paired t-test showed a significant difference between pre- and post intervention scores (p <0.05), while the qualitative data analysis identified key design principles for a gender-based media literacy program. The final model through the DBR process produces a framework for an adaptive, contextual, and gender-responsive digital media literacy program, which is not only relevant to Islamic educational institutions in Indonesia but can also be a global reference for the development of similar programs. The theoretical and practical contributions of this study include the development of design principles for gender-based media literacy programs that can be adapted in the context of Islamic higher education.